Effect of key parameters on jacalin extraction from aqueous phase into anionic reverse micelles - Sharifah Fathiyah, Sy Mohamad; Farhan, Mohd Said; Mimi Sakinah, A. M.; Shahril, Mohamad (Department of Chemistry, Universitas Gadjah Mada Yogyakarta, 2019)
This study demonstrates the extraction of jacalin from crude extract of jackfruit seeds using anionic surfactant based reverse micellar system, sodium bis(2-ethylhexyl) sulfosuccinate (AOT) in isooctane. Effects of various parameters, such as, NaCl concentration (0.05 – 1 M), pH of aqueous phase (pH 4 – 10), AOT concentration (5 – 150 mM), contact time (5 – 30 min) and phase volume ratio (0.5-5) on the transfer efficiency of jacalin was evaluated by changing one factor at a time (OFAT) while keeping the other parameters constant. A maximum of 83% of protein transfer was achieved after equal volume of organic and aqueous phase was stirred for 20 min using 20 mM AOT at pH 5 aqueous phase containing 0.1 M NaCl. The findings demonstrated AOT reverse micellar system as a promising and effective method to extract and purify jacalin from crude protein mixture.